REPRESENTASI TOLERANSI ANTARUMAT BERAGAMA DALAM FILM “JANGAN PANGGIL MAMA KAFIR” - Nisrina Audya Alexandra G.; Syifa Aulia; Naila Azizah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Film is one form of mass communication media that has a function not only as entertainment but also as a means of delivering social, cultural, educational, and moral messages to society. Through its storyline and characters, films can depict the reality of life occurring in social environments. One Indonesian film that addresses family life issues is "Jangan Panggil Mama Kafir" (Don't Call Mom a Kafir). This film depicts various conflicts occurring within the family due to differences in thinking, social environmental influences, and lack of communication among family members. This research aims to analyze the forms of family conflict, social values, and moral messages contained in the film. The research method used is a qualitative descriptive method with a content analysis approach. Data collection techniques were carried out by observing the storyline, dialogues, character behavior, and various important scenes in the film. The research results indicate that family conflicts in the film arise due to lack of openness and good communication among family members. Additionally, pressure from the surrounding environment also becomes a factor that escalates conflicts, making family relationships disharmonious. The film also contains various social values such as tolerance, love, care, patience, and responsibility. These values provide lessons to society about the importance of maintaining good relationships within the family. From an Islamic perspective, the moral messages in the film are in line with the teachings of the Qur'an and hadith which emphasize the importance of respecting parents, guarding one's speech, being patient, and assisting each other in goodness. Therefore, this film can be used as a social and moral learning medium for society, particularly in maintaining family harmony. When I started watching this film, I was immediately intrigued by its premise: a non-Muslim mother, Maria, married to Fafa, a Muslim man. After Fafa passed away, Maria committed to raising their daughter, Laila, in Islamic teachings. At first glance, it appears to be a typical interfaith conflict, but what makes this film compelling is how it presents love and tolerance as broader aspects that transcend mere differences in beliefs.